PEMBELAJARAN RECORDER DI SMP NEGERI 3 X KOTO SINGKARAK KABUPATEN SOLOK - Dwi Putri Purnama; Jagar Lumban Toruan; Esy Maestro (SENDRATASIK UNP, 2012)
The purpose of music Researchis to know about study recorder in SMPN 3 X Koto Singkarak, this type of research is qualitative research, that have done 9  times. The subjects of this research are class VIII A is pre-eminent class. From this research can conclude that study recorder is still not implemented yet. The teacher also not adabt the students ability with assign that has been given by the teacher, we can see from student mark on class VIII A are really unsatisfied. In the last meeting the teacher give an assignmnen for class VIII A that have 32 students, they get average of mark 65 Kata kunci: Pembelajaran, recorder, kelas VIII, SMPN 3, Kecamatan Singkarak